The correlation between age, body weight and testicular parameters in Murrah buffalo bulls raised in Brazil - Luz, Patrícia Aparecida Cardoso da [UNESP]; Santos, Paulo Ramos da Silva; Andrighetto, Cristiana [UNESP]; Jorge, André Mendes [UNESP]; Assis Neto, Antônio Chaves de [UNESP] (Japanese Society of Animal Reproduction, 2013)
Buffalo are an economically important source for meat and milk production, especially in Brazil. However, important aspects of their biology remain unknown thus far. Herein, we describe the biometric testicular parameters analyzed were scrotal circumference (SC), testicular weight (TW), testicular length (TL), testicular width (TWD), testicular thickness (TT) and testicular circumference (TC). Our data indicate strong correlations between SC, age and body weight, and additional significant relationships were identified between body weight, age and other testicular parameters. Thus, these parameters are suitable indicators when selecting bulls for breeding purposes.

Journal of Reproduction and Development Advance PublicationsAdvance Publication 2012-021 by J-STAGEAccepted for publication: August 19, 2012 Published online: September 14, 2012[Epub ahead of print]
Keywords: Buffalo reproduction; Feed management; Testis